Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

So the Tower of Hanoi numbers are given by the recurrence $h_n=2h_{n-1}+1$ and $h_1=1$. I let my generating function be $$ g(x)=\sum h_nx^n $$ Then $$ g(x)=\sum h_n x^n=\sum (2h_{n-1}+1)x^n=\sum 2h_{n-1}x^n+\sum x^n=2xg(x)+\frac{1}{1-x}. $$ Solving for $g(x)$ I find $$ g(x)=\frac{1}{(1-2x)(1-x)}=\frac{2}{1-2x}-\frac{1}{1-x}=2\sum (2x)^n-\sum x^n. $$ It seems then that the coefficient $h_n$ of $x^n$ is $2^{n+1}-1$, but wolfram mathworld says it should be $h_n=2^n-1$. What did I do wrong here? Thanks.

share|improve this question
    
What is the initial condition on the recurrence relation? –  Fabian Mar 4 '11 at 9:41
    
@Fabian, just added it. –  Dani Hobbes Mar 4 '11 at 9:42
    
It looks like wolfram's result has the right initial conditions and your result does not... –  Fabian Mar 4 '11 at 10:04

1 Answer 1

up vote 6 down vote accepted

Setting $$g(x) = \sum_{n=0}^{\infty} h_{n+1} x^n,$$ we obtain using $h_n = 2 h_{n-1} +1$ and $h_1 =1$ $$g(x) = \sum_{n=0}^{\infty} h_{n+1} x^n = h_1 + \sum_{n=1}^{\infty} (2 h_{n} +1) x^n = 1 + \sum_{n=0}^{\infty} (2 h_{n+1} +1) x^{n+1} =1 +2 x g(x) + \frac{x}{1-x}.$$ Solving for $g(x)$, we obtain $$g(x) = \frac{1}{(1-x) (1-2x)} = \frac{2}{1-2x} - \frac{1}{1-x} = \sum_{n=0}^{\infty} (2^{n+1} -1) x^n$$ such that $h_n = 2^n -1$.

share|improve this answer
    
Thanks Fabian, I should have been more careful with my indexing. –  Dani Hobbes Mar 4 '11 at 21:55

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.